(untitled) (Research, Society and Development, 2023)
The present study aims to carry out a literature review on the control of vertical transmission in patients living with HIV throughout the pregnancy-puerperal cycle, seeking to present the main findings and discussions within contemporary science, in order to avoid cases of HIV transmission. mother-child binomial. It is, therefore, a bibliographic review, of an integrative nature, built from scientific articles published in the last five years (2017-2021). 109 articles were obtained, of which 16 were read in full and were part of the final selection for this study. The analysis of the articles enabled the perception that vertical transmission represents an important challenge for the care of pregnant women with HIV within the health system, especially considering the deficient access to policies that guarantee the protection of reproductive rights and the promotion of sexual health, taking into account considering that the motherhood of women living with HIV presents a great social stigma. Therefore, from the analysis raised, it was possible to conclude that there is a limitation in the amount of information available about HIV in Brazil, which demonstrates the real need to encourage further research on this topic, allowing professionals to have access to epidemiological information and data more consistent with the local context.